Sublime enjoyment : on the perverse motive in American literature - Foster, Dennis A. (Cambridge studies in American literature and culture., 1997)
"Linking classic American literature to contemporary popular culture, Sublime Enjoyment argues that the rational systems of normal social life are motivated and sustained by "perverse" desires. This perversity arises from the failure of symbolic satisfactions - love, work, success - to make us happy, and from our refusal to accept that failure. Hoping to achieve satisfaction, we respond ultimately to situations that evoke older, more primary drives and their attendant emotions. But while a conventional pervert knows exactly what to want, the healthy pervert must find enjoyment inadvertently: in the abject or the sublime, in duty and reason, and in the obligations of a "fun morality." Examining the ways in which this inadvertence is represented in American literature and culture, Dennis Foster identifies ways that longings are linked to social forces."--Jacket